Letters To The Editor - Not Self-Sufficient, But Largest (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1952)
One item of general interest in MINING ENGINEERING Trends, May 1952 gives the wrong impression of the scale of the ilmenite operations in North Carolina It also implies there are known deposits of rutile which "guarantee self-sufficiency for many years" So far as we know this is not true At present, rutile is in such short supply in the United States that the Defense Mineral Authority is encouraging prospecting for new deposits So far none have been found of any consequence and our needs have to be met largely from the deposits near Jacksonville, Fla, and rutile imported from Australia JAY P WOOD VICE-PRESIDENT HUMPHREYS GOLD CORPORATION The reference to self-sufficiency was meant to apply to the ilmenite-bearing sands, not rutile, but improper phrasing failed to make this clear However, the press release that the Glidden Co circulated stated that this deposit of ilmenite was one of the largest in North America -Editor